ANALISIS CITRA MEREK, KESADARAN MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN (Survei Pada Konsumen Mayoutfit Bandung) - Anita Dewi Rachmawati, - (2021)
The Covid-19 pandemic that has occurred since December 2019 has also hit the micro, small and medium enterprises (UMKM) sector, especially in the fashion sector. Since the discovery of positive cases of Covid-19 in Indonesia, it has had an impact on consumer demand for fashion needs and this demand has decreased significantly. Currently, people prioritize the fulfillment of basic necessities and health products. This has an effect on decreasing people's purchasing power in fashion needs. Speaking of fashion, Bandung is one of the fashion central cities in Indonesia. One of them is a clothing line that is in demand by Bandung residents, especially for women, both teenagers and adult women. Mayoutfit is a clothing name in Bandung that provides fashion needs for women. Mayoutfit always provides all women's fashion needs with up to date models. The purpose of this study was to describe the brand image, brand awareness and product quality of Mayoutfit consumer purchasing decisions that represent Mayoutfit consumers in Bandung. The method used is an explanatory survey with a sample of 200 respondents, with a Non Probability Sampling Technique. Hypothesis testing in this study uses a structural equation model (Structural Equation Model / SEM). The results of this study indicate that the three variables, namely brand image, brand awareness and product quality, have a positive and significant effect on purchasing decisions. Keywords : Brand Image, Brand Awareness, Product Quality, Purchase Decision